MOTIF DETECTION IN INDONESIAN HAND-WOVEN FABRICS USING MATLAB - Haryanto, Agung; Purnomosari, Endah; Mulyani, Wiwiek Eka; Abdullah, Fadil; Putra, Valentinus Galih Vidia; Kusrianto, Adi (Politeknik META Industri Cikarang, 2025)
In our study, we developed an automated system for identifying Indonesian woven fabric motifs using MATLAB-based image processing. Procedures included obtaining visuals, enhancing quality, constructing a regional dataset, extracting features, measuring similarity, and analyzing colors. Correlation assessments enabled precise motif identification, while tailored color analysis improved similarity accuracy. The algorithm demonstrated effective recognition performance using dataset references. This approach offers a practical solution for cultural preservation, providing faster and more consistent results than manual evaluation